DIFFERENCES BETWEEN BIOCHEMICAL, HEMATOLOGICAL, AND COAGULATION PARAMETERS AMONG PATIENTS WITH MILD AND SEVERE COVID-19 - Hasanefendić, Berina; Dedić, Armina; Hajro, Sanela; Sehercehajic, Emir; Hajrović, Almedina; Alimanović-Alagić, Rubina; Smajlbegović, Velda; Ibričević-Balić, Lejla (Sanamed, 2023)
Introduction: COVID-19 is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 and causes a series of respiratory symptoms. Considering the appearance and development of symptoms, the course of COVID-19 can go from mild to severe. Depending on the course of COVID-19, the laboratory parameters change a lot, trying to defend the organism against the foreign pathogen and all the changes it causes.Therefore, the aim of this study is to observe the differences between biochemical, hematological and coagulation parameters depending on the disease stage of COVID-19 patients. Material and methods: We conducted a  cross-sectional study which included 160 COVID-19 patients from Sarajevo, Bosnia and Herzegovina. Biochemical, hematological and coagulation analyses were performed. Results: COVID-19 patients with a severe clinical course have higher average values of fibrinogen (6.53±4.47,p
Keywords: COVID-19; laboratory parameters; clinical course